Motivational interviewing for mental health clinicians : a toolkit for skills enhancement - Frey, Jennifer; Hall, Ali (Pesi Publishing, 2021)
"Conversations about change can be challenging. In this motivational interviewing (MI) toolkit, you will find a variety of tools and strategies designed to help you apply the spirit of MI so you can more effectively evoke people's own interests, experiences, and good ideas for change. Designed for mental health clinicians who want to deepen their learning and proficiency, this toolkit provides: examples of how to use MI to support people experiencing a variety of mental health issues, activities to help you more deeply explore the fundamental concepts, spirit, and tools of MI, sample conversation scripts that demonstrate the MI skills in practice, exercises to assess your progress and gain confidence in your skillst, ools to help you integrate MI more fully into your practice. Most importantly, this toolkit offers a variety of flexible opportunities for you to actively practice the core skills of MI: Use them on your own, with a partner, with a team of colleagues, or within an MI learning community."--